Five Key Factors for Students’ Success in Understanding the Subject of Al-Qur’an Hadith - Busthomi, Yazidul (Faculty of Islamic Sciences, Raden Rahmat Islamic University Malang, 2025)
The subject of Qur’an and Hadith is a crucial component of Islamic religious education, aiming to equip students with the ability to read the Qur’an fluently, translate its verses, comprehend its meaning, and memorize selected verses and hadiths. In madrasahs, the learning process emphasizes the development of fundamental skills related to the two primary sources of Islamic teachings: the Qur’an and Hadith. These skills include reading, writing, memorizing, translating, understanding, and applying the teachings in daily life. To achieve optimal learning outcomes, teachers must implement effective instructional methods and strategies This study found that students’ success in mastering the Qur’an and Hadith subject is influenced by five key factors: (1) high level of intelligence, (2) strong learning motivation, (3) genuine interest in the subject, (4) parental support, and (5) the use of suitable teaching methods by the teacher. Keywords: Five Key Factors, Students, Al-Qur’an Hadith